Landscape architect's pocket book - Vernon, Siobhan; Garmory, Nicola; Tennant, Rachel (Amsterdam : Elsevier, 2009)
1. Hard landscape 2. Soft landscape 3. Planning and legislation 4. Design Guidelines 5. General rules of thumb 6. Graphics
boek